A qualitative research on the present situation of nurses’ skills in pre-hospital treatment of severe trauma in Yunnan Province (云南省护士严重创伤院前救治技能现状的质性研究) - SHI Mei (史梅); WANG Chen (王晨); WANG Jun (王峻) (中西医结合护理)
Objective To explore the present situation of nurses’ skills in pre-hospital treatment of severe trauma in Yunnan Province, and to provide reference for the construction of trauma centers at all levels in Yunnan province and the training of pre-hospital first aid skills of nurses. Methods Nine experts from the Yunnan Trauma Center Construction Expert Committee were interviewed in a semi-structured way, and the data were processed and analyzed by Giorgi phenomenological analysis. Results Four themes were extracted: Nurses were indispensable to the pre-hospital treatment team. Nurses were found with low level of pre-hospital treatment skills and unclear responsibilities; Give the poor emergency response capability, it was urgent to standardize the treatment process. It was an urgent to establish scientific, objective and quantitative evaluation standard to improve nurses' pre-hospital treatment ability. Conclusion The pre-hospital first aid ability of nurses in Yunnan province is at a low level, and there is a lack of objective evaluation criteria. It is necessary to strengthen the training of nurses' pre-hospital treatment skills, clarify their treatment responsibilities, and construct the evaluation index of nurses' pre-hospital treatment skills for severe trauma, so as to provide scientific and objective reference for standardizing the pre-hospital treatment process and nurse training. (目的 探究云南省护士严重创伤院前救治技能现状, 为云南省各级创伤中心的建设和护士院前救治技能培训提供参考。方法 对云南省创伤中心建设工作专家委员会的9名专家进行半结构式深入访谈, 运用Giorgi现象学分析法进行资料处理与分析。结果 提炼出4个主题: 护理人员是院前救治团队中不可或缺的团队成员; 护士院前救治技能水平低, 岗位职责不明确; 应急能力弱, 规范救治流程迫在眉睫; 建立科学、客观、量化的评估标准是提高护士救治能力的迫切需求。结论 云南省护士整体院前救治能力弱, 缺乏客观评估标准, 必须加强护士的院前救治技能培训、明确救治职责, 且有必要构建护士严重创伤院前创伤救治技能评估指标, 为规范护士院前救治流程和培训提供科学的、客观的参考依据。)